Management of Eight ‘Ja’ for Economic Development of Nepal - Poudel, Durga (Journal of Comparative International Management)

(untitled) (None, 2008)
This paper proposes a theoretically grounded Asta-Ja framework of Eight "Ja" ─Nepali letter "Ja", Jal (water), Jamin (land), Jarajuri (plants), Janawar (animals), Jungle (forest), Jadibuti (medicinal and aromatic plants), Jalabayu (climate), and Jansakti (manpower) and referred to as Asta-Ja in Nepali language for economic development and management of Nepal. More concretely, it identifies and analyzes key elements of the framework to derive its implications for theory and policy development.